The effect of waxes, as a complement to hydrothermal immersion, on the quality of papaya fruit (Carica papaya L. Pococí hybrid) - V. Gustavo Corra; Gerardina Umaña (Agronomía Costarricense, 2015)
Different waxes were evaluated as a complement to hydrothermal treatment on the overall papaya fruit quality parameters. The fruits were harvested, washed in water, disinfected with sodium hypochlorite and exposed to hydrothermal immersion treatment at 49°C/20 min (HT); then treatments were applied: 1) bees wax +palm oil 5% solution; 2) fatty acids wax mixture 4.7%; 3) chitosan 0.1%; 4) only HT; 5) control (no hydrothermal immersion nor wax). The fruit was stored for 15 days at 12°C, then at 20°C. Significant differences (p≤0.05) were found between fruits receiving HT complemented with 5% bees + palm oil wax, which exhibited lower respiration rate (12.27 ml CO2/kg*h a 8 days after leaving cold storage), as compared with those receiving only HT (16.72 ml CO2/ kg*h) or control fruits (17.01 ml CO2/kg*h). The lesser percent of acumulated weight loss was registered whit TH plus bees wax cund palm oil. The color parameters were not affected, except for treatment 2, fatty acids wax mixture, which induced a delay in color development (p≤0.05). No changes were observed in internal or external firmness, nor in degrees brix. HT reduced the incidence of peduncular rot and anthracnose severity (p≤0.05), and extended useful life time. The use of waxes as a complement to HT can contribute to preserving some of the parameters which influence the final papaya fruit quality.